2006
DOI: 10.1021/ie060475k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Nonequilibrium and Multilayer Adsorption and Desorption of Gases on Solids

Abstract: A novel approach to the characterization of dynamic interactions of gases with solid surfaces is developed. A model is developed to represent the simultaneous adsorption and desorption processes in these systems. The model can simulate properties of nonequilibrium adsorption and desorption processes as well as the equilibrium state (isotherms and isobars). It also provides information on the distribution of loading of tightly bound molecules as the first layer on the surface as well as loosely bound physisorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…We now consider how realistic these models are in the context that under realistic ALD conditions such a “dry ambient” is far from what actually occurs. In fact, it is well-known that water molecules may be adsorbed from the gas phase forming multilayers on the surfaces of various oxides, such as Al 2 O 3 , TiO 2 , SiO 2 , SnO 2 , ZrO 2 , and HfO 2 . , It is found that the first adsorbed layer is strongly bonded to the surface by chemisorption and that the second layer is strongly bonded to the first chemisorbed layer by physisorption. Additional layers are all physisorbed with slowly diminishing bonding strength that approaches the bonding strength of liquid water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now consider how realistic these models are in the context that under realistic ALD conditions such a “dry ambient” is far from what actually occurs. In fact, it is well-known that water molecules may be adsorbed from the gas phase forming multilayers on the surfaces of various oxides, such as Al 2 O 3 , TiO 2 , SiO 2 , SnO 2 , ZrO 2 , and HfO 2 . , It is found that the first adsorbed layer is strongly bonded to the surface by chemisorption and that the second layer is strongly bonded to the first chemisorbed layer by physisorption. Additional layers are all physisorbed with slowly diminishing bonding strength that approaches the bonding strength of liquid water.…”
Section: Resultsmentioning
confidence: 99%
“…Additional layers are all physisorbed with slowly diminishing bonding strength that approaches the bonding strength of liquid water. ZrO 2 and HfO 2 show especially high adsorption loading due to their higher polarity and higher site density . Hence, under high water partial pressures, such as occurs during the water pulse of HfO 2 ALD, it is quite likely that several layers of water molecules will be accommodated on the HfO 2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…The major advantage of this model compared with the adsorption models reported previously [ 5 , 26 30 ] is that it includes spatial heterogeneity and also considers growth of the surface due to absorbed material in the explicit form. Although this feature is critical for thrombus growth, this model can also be of importance for many other fields, such as physics, chemistry, and biology.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of theoretical adsorption reaction models [11][12][13][14][15][16][17][18], based on the Langmuir [19,20] or BET [21] isotherms, (in the case study of the BET kinetic model, a simple analytical solution has only recently been found [22]), as well as theoretical adsorption diffusion models, based on second law. The adsorption diffusion models [23][24][25][26][27][28][29] are differentiated by the possible combinations of the three diffusion steps that govern the overall process: (i) liquid film diffusion, (ii) pore diffusion and (iii) surface diffusion.…”
Section: Introductionmentioning
confidence: 99%